2020
DOI: 10.1177/0146167219897662
|View full text |Cite
|
Sign up to set email alerts
|

(How) Do You Regret Killing One to Save Five? Affective and Cognitive Regret Differ After Utilitarian and Deontological Decisions

Abstract: Sacrificial moral dilemmas, in which opting to kill one person will save multiple others, are definitionally suboptimal: Someone dies either way. Decision-makers, then, may experience regret about these decisions. Past research distinguishes affective regret, negative feelings about a decision, from cognitive regret, thoughts about how a decision might have gone differently. Classic dual-process models of moral judgment suggest that affective processing drives characteristically deontological decisions to reje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…In particular, it is possible that reduced norm adherence in the moral judgments of people with elevated psychopathic traits results from lack of remorse and reduced care for others. This idea is broadly consistent with prior research linking norm-adhering judgments to empathic concern (Körner et al, 2020) and feelings of regret (Goldstein-Greenwood et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…In particular, it is possible that reduced norm adherence in the moral judgments of people with elevated psychopathic traits results from lack of remorse and reduced care for others. This idea is broadly consistent with prior research linking norm-adhering judgments to empathic concern (Körner et al, 2020) and feelings of regret (Goldstein-Greenwood et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Still, in the case of morality, there are a number of such theories highlighting slightly different forms of a dualprocessing distinction. Here we compare MJAC with three theories, each with a slightly different take on the dual-processing view: Greene's dual-process model (Greene, 2008(Greene, , 2016Greene et al, 2001Greene et al, , 2004; more recent, "softer" interpretations of Greene's approach (Byrd & Conway, 2019;Conway et al, 2018;Conway & Gawronski, 2013;Goldstein-Greenwood et al, 2020); and the model-based/model-free interpretation proposed by both Cushman (2013) and Crockett (2013).…”
Section: Examining the Explanatory Power Of Mjacmentioning
confidence: 99%
“…Supporting this idea, one study showed that experiencing higher regret was negatively correlated with utilitarian choices (Szekely & Miu, 2015). Another work found that endorsing the utilitarian (vs. deontological) judgments induced more affective (rather than cognitive) regret (Goldstein-Greenwood et al, 2020). Experiencing other post-decisional negative emotions such as guilt, shame, anger, and disgust have also been reported in sacrificial moral dilemmas (Pletti et al, 2016).…”
Section: Moral Dilemmasmentioning
confidence: 92%